2009
DOI: 10.1001/archpediatrics.2009.94
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Supplementation in Full-term Neonates

Abstract: Objective: To systematically review randomized controlled trials evaluating the efficacy and safety of prebiotic supplementation in full-term neonates. Data Sources: Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, and CINAHL databases and proceedings of relevant conferences. Study Selection: Eleven of 24 identified trials (n=1459) were eligible for inclusion. Intervention: Trials comparing formula milk supplemented with or without prebiotics, commenced at or before age 28 days and continued fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 49 publications
3
39
0
3
Order By: Relevance
“…44 According to a systematic review from 2009, 10 publications evaluated the effect of prebiotics on growth during the first year of life. 45 None of these trials showed a significant difference in growth parameters; infants fed the supplemented formula had slightly better weight gain (weighted mean difference, 1.07 g; 95% CI, 0.14-1.99; 4 RCT). 45 In conclusion: prebiotic oligosaccharides are unlikely to stimulate growth.…”
Section: Prebiotics and Growthmentioning
confidence: 95%
“…44 According to a systematic review from 2009, 10 publications evaluated the effect of prebiotics on growth during the first year of life. 45 None of these trials showed a significant difference in growth parameters; infants fed the supplemented formula had slightly better weight gain (weighted mean difference, 1.07 g; 95% CI, 0.14-1.99; 4 RCT). 45 In conclusion: prebiotic oligosaccharides are unlikely to stimulate growth.…”
Section: Prebiotics and Growthmentioning
confidence: 95%
“…116,117 BF infants generally have lower fecal pH and softer and more frequent stools compared to FF infants 91,92,118 ; therefore, several clinical studies have evaluated the influence of prebiotics on stool characteristics of infants (Table 2). Infants fed formula supplemented with GOS (2.4 or 4.4 g/L) had lower fecal pH, as seen in BF infants, in comparison with infants fed non-supplemented formula.…”
Section: (Us)mentioning
confidence: 99%
“…107,108,112,113 The effect of prebiotics on stool frequency and consistency has been evaluated in a systematic review. 117 Four randomized controlled trials reported that the stool frequency of infants fed prebiotics was similar to that of BF infants and was higher than that of infants fed control formula. 117 In addition, six studies assessed the stool consistency after prebiotic supplementation, and all reported that the stools were softer in infants consuming prebiotics.…”
Section: (Us)mentioning
confidence: 99%
See 2 more Smart Citations